High-Efficiency Wireless Power Transfer for Electric Vehicles: A Coil Geometry and PSO-Based Optimization Framework - Tarek S. Hassan; Mohamed M. Zakaria Moustafa; Nabil H. Abbasy (IEEE Access)
This paper investigates the optimization of wireless power transfer (WPT) systems for electric vehicle (EV) charging applications using a combination of analytical modeling, numerical simulation, and particle swarm optimization (PSO). A comprehensive mathematical model is developed for the electromagnetic (EM) coil, incorporating key geometrical parameters and accounting the presence of a ferrite core. This model is integrated with a PSO algorithm to maximize the power transfer efficiency (PTE) by identifying the optimal coil geometry. The optimized parameters are subsequentially applied to a double-sided inductor-capacitor-capacitor (LCC) compensation WPT system. Additionally, a sensitivity analysis is conducted to evaluate the influence of various design parameters on system performance and to identify critical parameters for robust operation. The proposed approach successfully captures the complex relationships among coil geometry, ferrite material characteristics, and system operating conditions, leading to high-efficiency outcomes. Optimization results reveal AC-side efficiencies up to 99.5% for identical coils at a 100 mm air gap, with performance exceeding 98% at 150 mm and 200 mm. For non-identical coils, efficiencies range from 97.1% to 98.45% across the same air gap range. To validate the proposed design, a full-system simulation model is developed, incorporating inverter and rectifier losses, while operating at a frequency of 85 kHz with a coil air gap of 150 mm. Under perfect alignment ( ${X}=0$ mm, ${Y}=0$ mm), the system achieves a peak DC-side efficiency of 96.9% with a coupling coefficient of 0.43. Under 150 mm lateral misalignment (corresponding to a coupling coefficient of 0.3), the system maintains a high DC-side efficiency of 95.47%.